Cdc42 in osterix-expressing cells alters osteoblast behavior and myeloid lineage commitment - Wirth, Franziska; Huck, Katrin; Lubosch, Alexander; Zöller, Caren; Ghura, Hiba; Porubský, Štefan; Nakchbandi, Inaam (Bone, 2021)
Osteoblasts are not only responsible for bone formation. They also support hematopoiesis. This requires responding to cues originating from several signaling pathways, a task performed by Rho GTPases. We therefore examined several transgenic mouse models and used inhibitors of Cdc42 in vitro. Deletion of Cdc42 in vivo using the Osterix promoter suppressed osteoblast function, while its deletion in differentiating osteoblasts using the Collagen-α1(I) promoter decreased osteoblast numbers. In both cases, bone mineral density diminished confirming the importance of Cdc42. Evaluation of hematopoiesis revealed that deletion of Cdc42 using the Osterix, but not the Collagen-α1(I) promoter increased the common myeloid progenitors (CMPs) in the bone marrow as well as the erythrocytes and the thrombocytes/platelets in peripheral blood. Causality between Cdc42 loss in early osteoblasts and increased myelopoiesis was confirmed in vitro. Work in vitro supported the conclusion that interleukin-4 mediated the increase in myelopoiesis. Thus, Cdc42 is required for healthy bone through regulation of bone formation in Osterix-expressing osteoblasts and the number of osteoblasts in differentiating osteoblasts. In addition, its expression in early osteoblasts/stromal cells modulates myelopoiesis. This highlights the importance of osteoblasts in regulating hematopoiesis.
Available online 13 August 2021
Gesehen am 20.12.2021